Peran Kepemimpinan Kepala Sekolah dalam Lembaga Pendidikan Islam di MTs Al-Jihad Medan - Rizki Akmalia; Arimbi Syahkila; Mela Safitri Situmorang; Nur Dahyanti; Tri Suci Apriani Harahap; Syahpan Ramadhan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to explain the leadership of the school principal at MTs Al-Jihad Medan. The method used in this research is descriptive research using qualitative data obtained from interviews, observations, and documentation. The results found that leadership and education are two different things. Leadership itself means a main object that has an influence on other objects, while education is an effort to create a learning atmosphere and learning process so that students can absorb or acquire something new, whether it be knowledge or experience. In this opportunity, the researcher will discuss leadership in the integrated Islamic school education institution. In the Islamic education institution at Mts Al Jihad Medan, leadership plays an important role and has a great responsibility as the main driver and motivator for the organization it leads. In its leadership system, it must have its own role to facilitate the movement of leadership and also to facilitate the achievement of the leadership's vision and mission. Leadership will be considered successful if its leadership is directed according to the initial goals of the organization. So, both leadership and education are important and interesting things to discuss comprehensively, so that we can also have the attitude and knowledge of a leader, especially in the world of education.